NILAI-NILAI PRIBADI KONSELOR DALAM PRIBADI KIAI - Hanik Mufaridah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
Values ​​include individual attitudes, as a standard of action and belief. And among the competencies that must be possessed by a counselor is personality competence. The purpose of this study is to find out and describe the similarities and differences in the counselor's personal values ​​contained in Carl Rogers' theory of person centered therapy with the personal values ​​contained in Kiai As'ad. The results show that the similarities are respecting individuals and humility; psychological knowledge and expert communication; harmony or authenticity and firmness hold the principle; and unconditional and sincere positive attention in charity and struggle. While the difference is Carl Rogers (objectivity, self-understanding, and accurate empathic understanding) and Kiai As'ad (zuhud and modest, fighters, time discipline and istiqomah, independent living and maintaining cleanliness, fond of building for the interests of religion and nation, attaching importance to interests people, and affection.